Deciphering the Genetic Basis of Lodging Resistance in Wild Rice Oryza longistaminata - Long, Weixiong; Dan, Dong; Yuan, Zhengqing; Chen, Yunping; Jin, Jie; Yang, Weilong; Zhang, Zhihong; Li, Nengwu; Li, Shaoqing (Frontiers in Plant Science, 2020)
The abuse of fertilizer results in tall rice plants that are susceptible to lodging and reduced plant yield. Hence, it is important to identify and utilize the quantitative trait loci (QTLs)/genes for lodging resistance breeding. Oryza longistaminata exhibits a strong stem and high biomass productivity, which could be a candidate gene pool for cultivars lodging resistance improvement. Here, a set of 152 BC2F20 lines derived from a cross between a cultivated line 93-11 and O. longistaminata was evaluated for lodging resistance. QTL mapping analysis combined with single-nucleotide polymorphism (SNP) marker derived from high-throughput sequencing identified 12 QTLs for stem diameter (SD), 11 QTLs for stem length (SL), and 3 QTLs for breaking strength (BS). Of which, 14 QTLs were first identified from O. longistaminata. A major QTL, qLR1, which was delimited to a region ∼80 kb on chromosome 1, increased stem diameter, stem length, and breaking strength. Another major QTL, qLR8, that was delimited in an interval ∼120 kb on chromosome 8, significantly enhanced the breaking strength. These results provide evidence that O. longistaminata can be exploited to develop lodging-resistant rice lines.